Clopidogrel monotherapy following dual antiplatelet therapy in patients with acute coronary syndrome post-drug-eluting stent implantation: a systematic review and direct/indirect treatment comparison. (3rd October 2022) - Sibbing, D; Shan, J; Bourhis, F; Hofer, K; Kasireddy, E; Qian, A; Khan, I
Abstract: Background: In patients with acute coronary syndromes (ACS) receiving a drug-eluting stent (DES), treatment with dual antiplatelet therapy (DAPT) reduces the risk of recurrent ischemic events. Optimal duration of DAPT depends on patient characteristics and switching to single antiplatelet therapy (SAPT) is recommended after the course of DAPT. Purpose: The aim of this study was to evaluate the comparative efficacy and safety of switching to clopidogrel SAPT following DAPT in patients with ACS post DES-implantation. Methods: A systematic literature review (SLR) was conducted by searching MEDLINE®, Embase, and CENTRAL up to July 27, 2021. Randomized controlled trials (RCTs) and observational studies that evaluated clopidogrel SAPT following DAPT in adults with ACS post-DES implantation were included. Heterogeneity of included studies was vetted in a feasibility assessment. Random effects meta-analyses were conducted using the metafor package for R. Direct comparisons were conducted for clopidogrel vs. aspirin and clopidogrel vs. DAPT. Using the Bucher method, aspirin vs. DAPT was indirectly compared by taking the difference between their respective pooled treatment effects vs. clopidogrel. A sensitivity analysis was conducted by including studies with a follow-up of 12 months. Results: Of 5, 349 records identified, seven unique studies (four RCTs and three observational studies) were eligible to be included in the SLR and quantitative treatment comparison. Risk of major adverse cardiovascular events (MACE) was lower in patients who switched to clopidogrel SAPT after DAPT compared with those who switched to aspirin monotherapy (hazard ratio [HR]: 0.72; 95% confidence interval [CI]: 0.54, 0.98), and this difference was significant. No significant difference in risk of MACE was found between switching to clopidogrel SAPT after DAPT and continuation of DAPT (HR: 0.90; 95% CI: 0.65, 1.25). This finding was consistent with the sensitivity analysis representing studies with follow-up of 12 months (HR: 0.95; 95% CI: 0.69, 1.31). Risk of bleeding was not analysed due to insufficient data across included studies for patients with ACS. However, within-study findings from one RCT of 4, 136 patients demonstrated a significantly lower risk of bleeding, defined as thrombolysis in myocardial infarction (major and/or minor, for switching to clopidogrel SAPT following DAPT compared with continuation of DAPT (0.54% vs. 1.17% of patients had bleeding [HR: 0.46; 95% CI: 0.23, 0.94]). Conclusion: Findings from this SLR suggest switching to clopidogrel SAPT after DAPT in ACS post-DES implantation has a lower risk of MACE compared with switching to aspirin monotherapy, and no difference in the risk of MACE compared with continuation of DAPT. There was insufficient data across the included studies to evaluate the bleeding risk, however, a single study indicated a lower bleeding risk with switching to clopidogrel SAPT. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Sanofi